The Effect Of Vitamins A, E, C On Skin Affected By Biological Age - Pierrotte, Oceane; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2023)
Mature skin affected by biological age is characterized by a decrease in skin turgor, the appearance of wrinkles, hyperpigmentation, prominent capillaries, and it is in need of cosmetic products. Non-invasive skin treatments with active ingredients help to restore the condition of mature skin. Retinol helps with pigment spots and improves skin elasticity. By interacting with the antioxidant L-Ascorbic acid, tocopherol protects the skin from ultraviolet rays and free radicals, prevents skin dehydration, and reduces wrinkles.The aim of the study. To analyse the effect of active substances of vitamins A, E, C on skin affected by biological age.Methods. The age of the study participants with mature skin affected by biological age is between the ages of 45 and 55. An adapted client card was used for the study, filled in before and at the end of the procedures. The structure of the complexion, skin type, problems, factors affecting changes in skin were assessed. Skin colour, turgor, epidermal moisture level, face skin tone, changes in skin pigmentation and wrinkles were observed and evaluated. Photo fixation was performed twice before and after the course of procedures, the data were archived and analysed. A lamp-loupe was used for visual examination of the facial skin.Results. The effect of active substances on the skin affected by biological age is different, and a longer course of face skin treatments is needed to confirm the results. Active substances with antioxidant properties lighten the complexion and strengthen the capillary walls. The effect of other active substances is aimed at the regenerative processes of the complexion.
Keywords: biological age; mature skin; retinol; tocopherol; L-Ascorbic acid